1997
DOI: 10.1039/a702063e
|View full text |Cite
|
Sign up to set email alerts
|

Bluemoon simulations of benzene in silicalite-1 Prediction of free energies and diffusion coefficients

Abstract: Constrained reaction coordinate (Bluemoon) dynamics have been used to characterise the free energy proÐle of benzene in silicalite-1 at 300 K along the mean reaction path for di †usion. The reaction path was found empirically by Ðtting a parametric curve through the mean positions of the benzene centre of mass. Both rigid and Ñexible zeolite lattices have been investigated. In both cases the primary adsorption site was located at the intersection of the straight and sinusoidal channels. Two other distinct adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 21 publications
7
65
0
Order By: Relevance
“…[33][34][35][36] For activated processes involving very high barriers this is the only suitable method because it would be impractical to follow a single long trajectory spanning several rxn to obtain an accurate c͑t͒. Nevertheless we found that, for barriers up to 5k B T and for the reaction complex model adopted, following a single equilibrium trajectory for fairly long times is a very simple and direct way to obtain both the true rate constant and its TST approximation.…”
Section: Model Methods and Calculationsmentioning
confidence: 95%
“…[33][34][35][36] For activated processes involving very high barriers this is the only suitable method because it would be impractical to follow a single long trajectory spanning several rxn to obtain an accurate c͑t͒. Nevertheless we found that, for barriers up to 5k B T and for the reaction complex model adopted, following a single equilibrium trajectory for fairly long times is a very simple and direct way to obtain both the true rate constant and its TST approximation.…”
Section: Model Methods and Calculationsmentioning
confidence: 95%
“…This technique has been applied to compute the diffusion coefficient for a large number of systems. 51,150,194,[268][269][270][271][272][273] These studies differ in the way the free energy of the barrier is computed. June et al 274 used a numerical technique to compute the partition function.…”
Section: Rare Event Simulations and Kinetic Monte Carlomentioning
confidence: 99%
“…In both these simulations the host-lattice is assumed to be rigid, which, especially in situations where the diameter of the largest pore is of dimensions similar to the diffusing molecule, can significantly affect the predicted magnitudes of the transport barriers. [8][9][10][11] For H 2 in all-silica sodalite we have explicitly demonstrated that this effect is significant 12 and, thus, in this study, the hopping rate of molecular hydrogen is calculated by means of moleculardynamics calculations with a fully flexible all-silica sodalite framework. Simulations are performed at a number of temperatures throughout the region from 700 to 1200 K and from the determined hopping rate the self-diffusion coefficient is calculated based on transition state theory ͑TST͒.…”
Section: Introductionmentioning
confidence: 76%